Navigating Pastoral Grief: An Analysis of I Thessalonians 4:13 and Pixar's Coco (POIMEN Jurnal Pastoral Konseling, 2025)
A wise sentence states that fear cannot stop death, but rather stops life. Through this wise sentence, it can be learned that fear of death is actually useless and can even cause harm. This applies to all forms of death, including the death of a loved one. In theology, there is a term known as Pastoral Grief which seems to be the branch of theology that deals most with grief that arises due to death. Pastoral Grief's efforts to overcome grief become increasingly difficult when many parties put forward the concept of "forgetting" as the best way to recover from grief. So this study attempts to provide a solution to this problem by examining I Thessalonians 4:13 and the film Coco. The method chosen in this study is qualitative with a comparative approach. In this case, the Bible text of I Thessalonians 4:13 will be compared with the narrative of the film Coco. Cross-Textual Hermeneutics by Archie Lee will be used as an interpretation method in this study. The selection of this method is based on efforts to appreciate the perspective of Asians in reading the Bible text, while freeing the Bible text from the tendency of biased readings that are still oppressed by western colonialism. Through this research, it is expected that new patterns and approaches will be found that can be used as strategies in Pastoral Grief services. It is also expected that the results of this study will provide a new color in viewing grief which has always received a negative stigma. It is also hoped that this study can have an impact on church services in an effort to maximize Pastoral and Counseling services, including Pastoral Grief.